Sensory-Based Interventions in the School Setting: Perspectives of Paraeducators - Lyn K. Kaiser; Marie-Christine Potvin; Caitlin Beach (Scholarworks @ WMU, 2020)
Background: The purpose of this study was to explore paraeducators' perceptions of sensory-based interventions (SBIs). Paraeducators are frequently responsible for implementing SBIs to enhance a student's ability to learn in school. Previous studies have explored the perceptions of teachers and occupational therapists, but as of yet, there are no published studies exploring the perceptions of paraeducators regarding the efficacy of SBIs. Methods: An ethnographic study was conducted with paraeducators (n = 11) working with students diagnosed with autism spectrum disorder or emotional disturbance in a center-based special education program. These paraeducators participated in a focus group or an interview that was transcribed and coded using a multi-step process. Results: The paraeducators reported implementing a variety of SBIs following a specific schedule designed for each child and on an as needed basis. They expressed that benefits of SBIs included improved student engagement, emotional and behavioral control, and increased time available to learn. Finally, the paraeducators mentioned that there are barriers to implementing SBIs in schools, such as availability of supplies and space. Conclusion: The study's findings suggest that paraeducators routinely implement SBIs, describe them as helpful for students, but acknowledge that barriers to implementation do exist.